Management of non-tubal ectopic pregnancies: rural tertiary care centre experience - Dwivedi, Namika; Mahajan, Mamta; Gupta, Amit; Vij, Anju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Non-tubal ectopic pregnancies are rare but potentially life-threatening conditions. Nearly 95% of ectopic pregnancies are implanted in the various segments of fallopian tube. The remaining 5% implant in non-tubal sites like ovary, cervix, rudimentary horn, cesarean scar, abdominal and even heterotopic. Seven patients with non-tubal ectopic pregnancy at rural tertiary institute at Dr. RPGMC Tanda, from February 2020 to January 2021 were included in the study. Demographic details, symptoms, beta human chorionic gonadotrophin (β-hCG) levels, ultrasound findings, management and treatment outcomes were presented. Medical treatment and surgical procedure, alone or combined, resulted in effective treatment in women with early diagnosis of non-tubal ectopic pregnancy and two patients had live birth (heterotopic and abdominal pregnancy). In our study, we report two cases of ovarian pregnancy, one case of rudimentary horn successfully managed surgically, one case of LSCS scar pregnancy managed medically with methotrexate followed by suction and evacuation, one case of cervical pregnancy managed by D&C, one case of heterotopic pregnancy managed surgically and abdominal pregnancy managed surgically. In this paper we report a single centre experience in the management of non-tubal ectopic pregnancy Early diagnosis of ectopic pregnancy especially non tubal ectopic, requires a high index of suspicion and availability of point of care, transvaginal USG. Accurate diagnosis and timely intervention will help reduce maternal morbidity, mortality and preserve future fertility.